Nucleoli in peripheral blood lymphocytes of patients with chronic lymphocytic leukemia treated with cytostatic drugs - Kopeć, J; Sitarska, E; Leszko, B (Archivum Immunologiae et Therapiae Experimentalis, 1983)
Quantitative and morphological changes of the nucleoli in the lymphocytes were studied in patients with chronic lymphocytic leukemia treated with cyclophosphamide and vinblastine, and were compared with the lymphocytes of patients treated with leukeran and healthy subjects. The nucleolar index was 1.20 in the lymphocytes of patients with chronic lymphocytic leukemia in stages II, III and IV of the disease, according to Rai's classification, and it showed no significant correlation with the mode and effect of treatment. The index was significantly higher than in the lymphocytes of healthy subjects (p less than 0.05). The activity of nucleoli in the lymphocytes of the patients treated with cyclophosphamide with vinblastine was significantly higher than in the leukeran-treated patients and healthy subjects, and it increased with progression of the disease and with successive passage from stage II to III and IV. In the patients in whom clinical improvement was achieved and the treatment with cytostatics was withdrawn, the proportion of active nucleoli in the lymphocytes was decreased.